La yuca como cultivo principal de un sistema de cultivo multiple - Thung, M.; Cock, James H. (International Center for Tropical Agriculture, 1979)
Multiple cropping, sequential cropping, intercropping, mixed intercropping, intercropping in rows, in strips, relayed intercropping, cropping patterns, monoculture, crop rotation and land equivalent ratio are defined. The characteristics of multiple cropping and intercropping with beans are discussed; for the latter problems of competence are discussed (light, CO2, water and nutrients). Some cultural practices are recommended for cassava/bean intercropping: soil and fertilization type, water availability, propagation material, and weed, pest and disease control. (CIAT)